Cognitive and emotional information processing: protein synthesis and gene expression - Sajikumar, Sreedharan (Blackwell Publishing Ltd, 2007)
Recent findings suggest that functional plasticity phenomena such as long-term potentiation (LTP) and long-term depression (LTD) – cellular processes underlying memory – are restricted to functional dendritic compartments. It was also shown, however, that a relatively strong activation of a synaptic input can abolish compartment restrictions. Our data support these findings and we present one cellular pathway responsible for uncompartmentalization of the normally localized plasticity processes by the action of rolipram, an inhibitor of type 4 phosphodiesterases. In contrast with compartment-restricted information processing, uncompartmentalization requires transcription. In the search for system relevance of compartmentalization versus uncompartmentalization we describe firstly data which show that more cognitive information processing in rats' behaviour may follow rules of compartmentalization, whereas stressful, more life-threatening, inputs abolish compartment-restricted information processing involving transcription. Our findings allow us to suggest that consolidation of processes which take place during the cognitive event most probably depend on local protein synthesis, whereas stress immediately induces gene expression in addition, resulting in a compartment-unspecific up-regulation of plasticity-related proteins (PRPs), providing the entire neuron with a higher level of ‘reactiveness’. These data would provide a specific functional cellular mechanism to respond differentially and effectively to behaviourally weighted inputs.